Variation in the digestibility of amino acids in soybean meal from a single processing plant - D J Lee; C A Maloney; D W Dean; H Cao; Joe D Hancock; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2000)
Digestibilities of amino acids among samples of soybean meal (SBM) collected during a fall harvest season (4 collections made 15 d apart) were similar, except that true digestibility from tryptophan was lower for a sample collected on d 30 of the experiment vs SMB samples collected on the other dates. Our data suggest that proximate components and amino acid digestibilities of the SBM were very consistent and uniform during the 45 d of sample collection in one processing plant.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Soybean meal; Digestibility; Amino acids